Ascidians collected during the Madibenthos expedition in Martinique 3. Stolidobranchia, Pyuridae and Molgulidae - Monniot, Françoise (Zootaxa, 2018)
An inventory of the marine benthic fauna around Martinique was the aim of the European Madibenthos expedition 2016. Among a large number of invertebrates abundant ascidians were collected: the phlebobranchs and Styelidae among the stolidobranch were already studied and the results published (Monniot 2018a and b). A third group, belonging to the Pyuridae and Molgulidae (Stolidobranchia) is studied here; it includes 13 species, three of them recorded for the second time. Each of them is described and figured and the geographic distribution is given.